Violence against Women and Children during the Pandemic as Perceived by Barangay 8 South Caloocan: Vol. 3, No. 1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
One in every three women is subjected to physical or sexual violence, mostly perpetrated by an intimate partner. This study aims to determine the causes of violence against women and children during the pandemic in Barangay 8, South Caloocan. The researchers conducted this study by using a questionnaire with close-ended questions consisting of two parts: The first part contains a few questions about the participant's personal information, which would be optional for them to fill up or not; the second part contains two checklist questions about the pros and cons with four choices each that would help to determine the causes of violence against women and children.The result from data gathered from the 20 respondents on the other solutions offered to address the violence against women and children during the pandemic was encountered as "highly recommended."This study showed that violence against women can be avoided. The health sector has a critical role in providing comprehensive healthcare to women who have been victims of abuse and directing women to additional support services that they may require. Physical aggressiveness, sexual coercion, psychological abuse, and controlling behaviours are all examples of intimate relationship violence. "Any sexual act, an effort to get a sexual act, or other act directed at a person's sexuality using coercion, by anyone, regardless of their relationship to the victim, in any environment," according to the CDC. The solution should ensure that the women are in occupational health and safety, anti-discrimination laws give adequate protection to women affected by VAWC and provide the resources to guarantee training information and monitoring of these laws.